Peran Tokoh Agama dan Guru PAI dalam Penguatan Pemahaman dan Pengamalan Nilai-Nilai PAI Remaja di Desa Kota Agung Kecamatan Air Besi Kabuperten Bengkulu Utara - Alpiansyah Putra (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
Research problem formulation: 1) What are the factors that cause teenagers in Kota Agung village to behave deviantly? 2) What are the efforts made by religious leaders and PAI teachers to overcome the problem of adolescent deviant behavior in the village of Kota Agung? This study aims to determine the factors that cause adolescents in the village of Kota Agung to behave deviantly and the efforts made by religious leaders and PAI teachers to overcome the problem of deviant behavior of adolescents in the village of Kota Agung. The type of research used is descriptive qualitative. It is said to be descriptive qualitative because this study aims to describe the results of data processing in the form of words, general descriptions that occur in the field and the respondents in this study are religious leaders, PAI teachers and teenagers. Then the researchers also took secondary data as supporting data. The techniques used in data collection are observation, interviews and documentation. The research findings in this thesis are that there are several factors that cause adolescents in the village of Kota Agung to behave deviantly, namely: due to the opportunity for parents to talk and have fun by prioritizing an attitude of attention to their youth. And also the youth saw that bad behavior was not only displayed by their circle, but almost most of the parents in the village. As a result, they defend themselves that their parents, who should be an example, actually give bad behavior as well. Then the efforts made by religious leaders and PAI teachers in overcoming and also fortifying deviant behavior in the village of Kota Agung are still classified as still not being applied to teenagers in the village. As the researchers have obtained from various parent informants, some of them think it has been realized and generally most parents in the village complain about their lack of effort and role in guiding teenagers in this village to be able to fortify themselves from deviant behavior.